'I'm a Cloud of Infinitesimal Data Computation' When Machines Talk Back: An interview with Deborah Harrison, one of the personality designers of Microsoft's Cortana AI. (11th January 2019) - Young, Liam
Abstract : How is the personality of an artificial intelligence crafted, and what are the issues at stake? As one of the original architects of Microsoft's digital assistant Cortana's personality, Deborah Harrison knows the process inside out. In an interview with Guest‐EditorLiam Young, she examines the questions that creating this AI raised in terms of gender, culture and ethics, and considers the future of machine interactions. Wataru Sasaki, lead developer of the software behind the AI pop star Hatsune Miku, and android engineer Kohei Ogawa also join the discussion.